Protective and cross-protective mucosal immunization of mice by influenza virus type A with bacterial adjuvant - Zanvit, Peter; Havlícková, Martina; Tácner, Jaroslav; Novotná, Olga; Jirkovská, Marie; Cechová, Dana; Julák, Jaroslav; Sterzl, Ivan; Prokesová, Ludmila (Immunology letters, 2008)
Mucosal immunization by inactivated viruses often fails to evoke a sufficient immune response. Intensive efforts have been made to enhance the response by suitable adjuvants. We used the G+ nonpathogenic delipidated bacterium Bacillus firmus with pronounced immunostimulatory properties as an adjuvant for immunizing mice with inactivated influenza virus type A. BALB/c mice were immunized intratracheally with inactivated influenza A H1N1 and H3N2 viruses. The production of antibodies in sera and secretions was determined by the ELISA. The local situation in the lungs was assessed histologically and by testing the cytokine expression. The protective and cross-protective effect against infection was tested in in vivo experiments after infection with influenza virus A H1N1. B. firmus as adjuvant increased both systemic and mucosal antibody responses, improved protection against homologous virus and induced cross-protection against virus H1N1 after immunization with virus H3N2.
Keywords: myši; adjuvancia imunologická; myši inbrední BALB C; Influenza Vaccines; virus chřipky A, podtyp H3N2; lidé; vakcíny proti chřipce; Influenza, Human; Humans; Orthomyxoviridae Infections; zkřížené reakce; Influenza A Virus, H1N1 Subtype; Mice, Inbred BALB C; plíce; Mice; Bacillus; Animals; virus chřipky A, podtyp H1N1; cytokiny; protilátky virové; Adjuvants, Immunologic; infekce viry z čeledi Orthomyxoviridae; Cytokines; zvířata; imunizace; Immunity, Mucosal; Influenza A Virus, H3N2 Subtype; Lung; Antibodies, Viral; Immunization; slizniční imunita; chřipka lidská; ženské pohlaví; Female; Cross Reactions